Local Food Utilisation for the Prevention of Underweight and Chronic Energy Deficiency (CED) in Pregnant Women in Pancasan Area Bogor City - Resmi, Lussy Citra; Widianto, Dendy; Soedarmo, Erlin (Universitas Ibn Khaldun Bogor, 2025)
This study aims to improve community knowledge on underweight nutrition in toddlers and Chronic Energy Deficiency (CED) in pregnant women through education based on local food utilisation. The research was conducted in Pancasan area, Bogor City, using intervention method. The approach included a knowledge survey, in-depth interviews, and nutrition education using audiovisual media. The results showed a significant increase in participants' knowledge of balanced nutrition. The average pretest and post test results in the education activities for the underweight category increased from 53.80% to 74.28%, while for the SEZ category it increased from 63.04% to 86.52%. Success factors include the effectiveness of audiovisual media and interactive educational methods. This education is proven to be able to increase public awareness in the utilisation of local foods such as taro to prevent nutritional problems.